The Practice of infaq among UiTM Puncak Alam’s staff / Aima Mawaddah Ahmad Sanusi. - Ahmad Sanusi, Aima Mawaddah (2019)
Infaq generally means spending money in the way of Allah SWT. It is to provide valuable property to other people. Islam demands that its people use their wealth for good. The Muslim must accept the gift of sustenance from the Divine and He is the Supreme Owner to all of that. Infaq requires less mind preparation and the practice of infaq also cannot be cultivated without the reinforcement of self-esteem values a Muslim. Therefore, the practice of infaq is at the same time a preparation cultural, mental and spiritual. It is from this point of view that the researchers intend to study infaq practices among UiTM Puncak Alam employees. Researchers use quantitative questions to collect data. Hopefully the findings of this study will help improve further number of participants and amount of future infaq.